JENIS-JENIS RAYAP (INSEKTA: ISOPTERA) YANG TERDAPAT DI KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU PROVINSI RIAU - Santoso, Ridwan (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
Termites are social insects eating the cellulose that serves as an indicator of environmental changes. This study was aimed to determine the diversity of Termites species (Isoptera) in Bangun Purba Sub district Rokan Hulu District Province Riau. This study was conducted in Mei to November 2o15 by using survey metod. Sample were collected by Finding Colony and Casual Collelction with direct collection. Result showed that the termites belong to 3 families (Kalotermitidae, Rhinotermitidae and Termitidae, 7 subfamilies (Coptotermitinae Heterotermitinae Kalotermitinae Macrotermitinae Nasutitermitinae Rhinotermitinae Termitinae) ang 14 genera, namely is Bulbitermes, Coptotermes, Cryptotermes, Globitermes, Glyptotermes, Hospitalitermes, Macrotermes, Microtermes, Nasutitermes, Odontotermes, Pericapritermes, Reticulitermes, Schedorhinotermes dan Termes.